1991
DOI: 10.1007/bf02260433
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in the benthic habitat of the Maarsseveen Lakes system, The Netherlands

Abstract: The cadmium, zinc, lead and copper concentrations in benthic invertebrates and sediment were determined during two consecutive winters in the Maarsseveen Lakes system. A sequential extraction procedure was applied to estimate the bioavailability of the trace metals in the sediment. Based on the trace metal analyses of organisms and sediment, it is concluded that the Maarsseveen Lakes system has background levels of cadmium, zinc, lead and copper. As the majority of metals was present in geochemically more stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The internal lead concentrations of O. po/ymorpha from Lake Maarseveen land II (TIMMERMANS et al, 1991) and Lake Heerhugowaard (KRAAK et al, 1991 ) (all in The Netherlands) are in the same range as the internal lead concentrations in mussels from Lake Markermeer (0.8 _+ 0.5 mg.kg dw-1). These concentrations are lower than those found in Anodonta anatina from the river Thames (MANLY and GEORGE, 1977) and those found in Unio pictorum and Anodonta cygnea from Lake Balaton (SALANKI et al, 1982).…”
Section: Discussionmentioning
confidence: 86%
“…The internal lead concentrations of O. po/ymorpha from Lake Maarseveen land II (TIMMERMANS et al, 1991) and Lake Heerhugowaard (KRAAK et al, 1991 ) (all in The Netherlands) are in the same range as the internal lead concentrations in mussels from Lake Markermeer (0.8 _+ 0.5 mg.kg dw-1). These concentrations are lower than those found in Anodonta anatina from the river Thames (MANLY and GEORGE, 1977) and those found in Unio pictorum and Anodonta cygnea from Lake Balaton (SALANKI et al, 1982).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, water and sediment samples were analysed for (bioavailable) trace metals. It is concluded that, in comparison with other freshwater ecosystems, the macroinvertebrates in the Maarsseveen lakes have background levels of pollution (TIMMERMANS et al, 1991a). Adverse effects on biota, which could be expected based on preliminary observations (SWAIN eta/., 1987;VAN DONK, 1987), are therefore highly unlikely.…”
Section: Field Observationsmentioning
confidence: 95%
“…Other studies have documented gradients along elongated reservoirs and lakes in which clay and/or silt fractions and chemical constituents such as metals, phosphorus, or organic carbon increased with either increasing distance from the main inlet, increasing depth, or both (e.g., Sager and Pucsko 1991; Timmermans et al 1991;Reynolds 1999). Compared to lakes, reservoirs typically have an elongated geometry; they are shallow near the inlet with a regularly increasing depth towards the dam (Morris and Fan 1998).…”
Section: Sediment and Pore Water Chemistrymentioning
confidence: 97%